“Have You Taken the A4 Challenge?” Correlates and Impact of a Thin Ideal Expression From Chinese Social Media - Jackson, Todd; Ye, Xiaoxuan; Hall, Brian J.; Chen, Hong (Frontiers in Psychology, 2021)
In three studies, we assessed knowledge, correlates, and effects of the A4 challenge, an expression of the thin ideal from Chinese social media. In Study 1, gender differences in familiarity with the A4 challenge were assessed among 225 women and 151 men. Compared to men, women and female peers from participant social networks were more familiar with and likely to have taken the challenge themselves. In Study 2, body image experiences of women who passed the A4 challenge (N=45) and average weight peers who did not pass the challenge (N=75) were assessed. The former group reported fewer weight concerns and less social pressure to lose weight but no group differences were observed with respect to binge-eating, dieting, or other compensatory weight loss behaviors. As such, eating disorder symptoms did not account for the experience of passing the A4 challenge. In Study 3, changes in state body dissatisfaction were assessed among 205 women randomly assigned to view images of (1) thin peers successfully passing the challenge versus (2) thin or (3) average size controls. The absence of condition differences in post-exposure state body dissatisfaction indicated exposure to A4 challenge portrayals per se did not cause increases in negative appearance self-evaluations for women in general. However, among women who were exposed to A4 challenge images, but not control group women exposure to other images, trait body dissatisfaction predicted increased post-exposure state dissatisfaction, independent of pre-exposure state dissatisfaction. Implications are discussed in relation to effects of exposure to the A4 challenge and conceptualizing the task as a “challenge”.